KRISTOLOGI DALAM KONTEKS KEBUDAYAAN SUKU MIGANI DI PAPUA - Kleopas Sondegau (Studia Philosophica et Theologica, 2017)
Before Catholic Church entered in the land of Intan Jaya, Migani people already have positive values in their culture. These values are used as the basis and guidance of ethical, moral, spiritual, social and religious life. In such a situation of life, Christianity comes to proclaim Christ and His teachings to the people of Migani. Based on the proclamation of the local community began to re-dig the positive values in their culture. One of the values of culture raised is the life story and the work of a Peagabega figure whose life is similar to that of Jesus Christ. After making an effort to find a “meeting point” between Peagabega and the events of Jesus Christ, so they found a number of similar elements. With this effort the Migani people began to accept and recognize Peagabega as Jesus according to their own cultural pattern. Such an understanding does not intend to live a dualistic faith because Peagabega is only a means for Catholic Migani people to deepen the understanding of Jesus Christ more deeply. Sebelum Gereja Katolik masuk ke tanah Intan Jaya, masyarakat Migani sudah memiliki kearifan lokal (nilai) dalam kebudayaan mereka. Kearifan-kearifan ini digunakan sebagai dasar dan penuntun bagi kehidupan etis, moral, spiritual, sosial dan religius. Dalam perkembangan selanjutnya, Kristianitas hadir dengan menyerukan Yesus Kristus dan ajaran-Nya kepada masyarakat Migani. Berdasarkan kesadaran bersama, masyarakat setempat mulai menggali lagi kearifan-kearifan lokal dalam budaya mereka. Salah satu kearifan yang ditemukan adalah kisah hidup dan karya Peagabega yang sepertinya mirip dengan kisah hidup Yesus Kristus. Dengan usaha ini, masyarakat Migani mulai menerima dan mengakui Peagabega sebagai Yesus Kristus berdasarkan pola kebudayaan mereka. Pemahaman seperti ini pada dasarnya tidak bermaksud untuk menjalankan iman yang dualistik karena Peagabega hanyalah sarana bagi umat Katolik Migani untuk memperdalam pemahaman tentang Yesus Kristus